The diagnosis and treatment of donovanosis (granuloma inguinale). Issue 6 (December 1991) - Richens, J
Abstract : Donovanosis is a predominantly tropical cause of genital ulcer occurring chiefly in small endemic foci in all continents except Europe. Diagnosis requires the careful collection, staining and examination of smears or biopsies of characteristic genital and, occasionally, extragenital lesions for demonstration of the pathognomonic Donovan bodies (Calymmatobacterium granulomatis) within histiocytes. Successful isolation of C. granulomatis has rarely proved feasible, the last report being in 1962. Donovanosis has a characteristic histopathological picture which occasionally simulates epithelioma. The antibiotics reported as showing good activity in donovanosis are those with good activity against gram negative bacilli and whose lipid solubility ensures good intracellular penetration. They include streptomycin, chloramphenicol, erythromycin, lincomycin, cotrimoxazole and the tetracyclines. More recently, good results have been reported with norfloxacin and thiamphenicol. The treatment of donovanosis in pregnant women and patients with AIDS poses special problems. Complications of donovanosis such as elephantiasis, stricture and pelvic abscess may require surgery. Contacts should be traced for examination but only treated if lesions are found.